Secrets of RSS - Holzner, Steven, 1957- (Peachpit Press, 2006)
Whether you want to create your own RSS feeds or just would like to locate and add them to your Web site, this is the book for you. In the Secrets of RSS, author Steve Holzner provides real-world guidance and advice to introduce you everything you need to know about effectively implementing and using RSS: - How to connect to RSS feed, handle them, and track down what you want - The difference between RSS and blogs, and how nearly every major RSS reader works - How to design an RSS feed, what you'll find in RSS feeds, and formats and links - Create your own first RSS feed from scratch:and subscribe to it - Putting RSS to work in the real-world - The free tools and software available to help you create RSS files - Finding, subscribing to, and creating podcasts - Spreading the word about your RSS feed - RSS best practices - And more!